CHEMICAL ADDITIVE SUPERPLASTICIZER BETON STRONG - Kalıknazarova Amangul; Temuratova Gulbahar; Sultanova Ruhiya; Utepbergenova Maqpal (European Science Publishing, 2024)
BETON STRONG 27, Beton Strong 17 types of superplasticizers used in concrete production are superplasticizers. Annoin comparison with softeners on a naphthalenic basis of BETON STRONG 27 has higher plasticizing ability due to higher effect of a dispergation that allows to receive concrete mixes with the set parameters at lower value of the water-cement relation. This ability provides concrete mixes with high rates of early and final durability and also high rates on frost resistance, water tightness and mobility.
Keywords: Rocks, magmatic, metamorphic, igneous rocks